Blind Color Image Steganography in Spatial Domain - Abdullatif, F. A.; Shukur, W. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
With wide spread of internet, and increase the price of information, steganography become very important to communication. Over many years used different types of digital cover to hide information as a cover channel, image from important digital cover used in steganography because widely use in internet without suspicious. Since image is frequently compressed for storing and transmission, so steganography must counter the variations caused by loss compression algorithm. This paper describes a robust blind image steganography, the proposed method embeds the secret message without altering the quality by spraying theme on the blocks in the high order bits in color channel such blue "without altering the human vision system" and make them integral to cover. This method depends on constant sequence spread spectrum method and survives loss compression image like JPG.